Dinamika Pengelolaan Madrasah dalam Kesultanan Sambas, 1910-1945: Studi Kasus Madrasah Pedoman Islam - Sunandar, Sunandar (Department of History, Faculty of Humanities, Diponegoro University, 2023)
Madrasas, particularly Islamic religious schools, played a significant role in disseminating and practicing Islamic teachings within the Sultanate of Sambas. The image of madrasas in Sambas is embodied by two institutions established by the elite of the palace: Madrasah Sulthaniyah (1916) and Tarbiatoel Islam (1936), projecting an elite status within society. In 1936, alongside the establishment of Tarbiatoel Islam, a village madrasa named Madrasah Pedoman Islam was founded by ordinary residents outside the city of Sambas, catering to the Kampung community. However, management dynamics and ensuing issues led to the closure of these madrasas in favor of public elementary schools through the Inpres (Presidential Instruction) program. This paper employs a historical method, analyzing the periodization of Madrasah Pedoman Islam's development within its historical context. Data are sourced from manuscripts pertaining to Islamic Guidelines Madrasah. The study revealed that teachers of Madrasah Pedoman Islam, along with the community, sought solutions to the primary issue of financial constraints. One solution involved utilizing Zakat funds, including Zakat Fitrah and Zakat Māl, in the form of rice